(untitled) (Italian Journal of Public Health, 2003)
Background. In this article the results are presented of a four part study on the effect of screening for scoliosis and (repeated) well-care visits and freely accessible consultation hours at secondary schools, on the incidence and prevalence of (para)suicide, mental health, adolescent health compromising behaviour and lastly obesity. Methods. An ecologic case-referent study design was used with data from the Netherlands Bureau of Statistics, the Ministry of Defence, the 1992 High-School Student Study, all of the youth health care departments in The Netherlands and relevant censuses. Results. Attention to mental and physical health and health compromising behaviour, either during screening, open consultation hours or during well-care visits seems to be ineffective and in some instances even detrimental to youth health. Of the 18 different outcome measurements, 5 were significantly negative and none were significantly positive. Conclusions. This four part study does not support the hypothesis that on a population level, the preventive activities of youth health care departments such as screening for scoliosis, (more) frequent well-care visits or offering open consultation hours at secondary schools, have a beneficial effect on prevention of (para)suicide, poor mental health, health compromising behaviour or obesity.